SOSIALISASI PENGGUNAAN ZOHO SEBAGAI SISTEM INTEGRASI OMNICHANNEL DALAM MENINGKATKAN EFEKTIVITAS KINERJA DIVISI MARKETING DI PT INOVASI TEKNOLOGI SOLUSINDO - Yusuf Putra Wardhana; Ayundha Evanthi (Jurnal Pengabdian Masyarakat Sabangka, 2026)
The development of digital marketing requires companies to integrate various communication channels to enhance the effectiveness of customer interactions. One approach used is an omnichannel system that enables centralized communication management. This activity aims to improve the effectiveness of the marketing division's performance through the socialization and training of ZOHO as an omnichannel integration system. The method used in this activity includes preparation, socialization, system demonstration, and hands-on practice by participants. The materials presented cover the introduction of the omnichannel concept, the use of ZOHO's main features, and the management of customer communi cation across multiple channels within a single platform. The results are able to understand the concept of omnichannel and operate ZOHO to support marketing activities, such as responding to customers more quickly, managing contact data, and monitoring customer interactions in an integrated manner. Therefore, the use of ZOHO as an omnichannel system can improve the efficiency and effectiveness of marketing division performance.